The Death of Captain Wells - Dougall, Allan H. (Allan Houston), 1836-1912; Public Library of Fort Wayne and Allen County (Salt Lake City, UT : Project Gutenberg, 2021)
"The Death of Captain Wells" by Allan H. Dougall et al. is a historical account published in the mid-20th century. It recounts the dramatic events surrounding the life and death of Captain William Wells, a figure prominent in early American-Indian relations during the War of 1812. The narrative highlights the complexities of Wells' loyalties as he navigates his role as an Indian agent and a soldier, ultimately leading to his tragic fate during the massacre at Fort Dearborn. The book details Captain Wells' background, including his adoption by the Miami tribe and his later return to ally with American forces. It describes the events leading to the evacuation of Fort Dearborn, including Wells' attempts to thwart a disaster by encouraging the destruction of supplies that might inflame tensions with the Indians. As the evacuation unfolds, Wells and a small group of soldiers face overwhelming odds when they are ambushed by a much larger force of Potawatomi warriors. The narrative culminates in a fierce battle where Wells fights valiantly but ultimately falls to the overwhelming numbers of his opponents, leading to his brutal death. The account not only captures the violence of the conflict but also reflects on the complex relationships between Native Americans and settlers during a tumultuous period. (This is an automatically generated summary.)
Release date is 2021-07-21
Stephen Hutcheson and the Online Distributed Proofreading Team at https://www.pgdp.net
Keywords: Wells, William, 1770-1812